Development of the dementia attitude scale focusing on well-being - Ono, Ichie; Nakatani, Hisae; Inoue, Yuriko; Peng, Xuxin; Hamada, Hironobu (Frontiers in Psychology, 2024)
This study aimed to develop the Dementia Attitude Scale Focusing on Well-being (DASFWB) and to verify its reliability and validity. This scale measures the factors that individuals without dementia would consider important for their well-being if they were to develop dementia. It is expected to serve as a useful indicator for intervention strategies aimed at achieving an inclusive society. Methods: The draft DASFWB scale was developed by extracting stories from older adults with mild Alzheimer's disease. The questionnaire was distributed to 1,614 adults aged 65 and older who were able to complete the self-administered questionnaire. Data from 815 individuals who completed the questionnaire without help (58.8% valid response rate) were analyzed. Exploratory and confirmatory factor analyses were performed to identify the factors underlying the scale. Reliability was tested using Cronbach's alpha. Validity was tested through sample, criterion-related, convergent, and discriminant validity. Results: The development and validation of the DASFWB identified a three-factor, 12-item scale. Cronbach's alpha coefficients for the scale and its three factors were 0.857, 0.843, 0.723, and 0.644, respectively. The confirmatory factor analysis model indices were as follows: χ 2 =146.574, df =51, p<0.001, comparative goodness of fit index=0.930, goodness of fit index=0.945, Tucker-Lewis index=0.909, and root mean square error of approximation=0.068. The composite reliability value for convergent validity, which was greater than 0.7, was higher than the average variance extracted value. The criterion-related validity showed a weak correlation (ρ=-0.245-0.341, p<0.001). Discussion: The DASFWB exhibits good reliability and validity, indicating its utility as a measuring instrument.